Design and optimization of a quadrupedal dynamic disturbance force measurement platform using strain gauges. (1st April 2023) - Zhou, Chengbo; Xia, Mingyi; Xu, Zhenbang
Highlights: The platform uses four strain monopodia to enhance the load capacity and retain the good low frequency performance. RSM balance the sensitivity and stiffness of the measuring platform, and the precision is improved using D optimization. The design target and optimization approach was verified experimentally. Abstract: A novel quadrupedal dynamic disturbance force measurement platform is described for the measurement of the disturbance forces of low-frequency sources in large optical facilities on the ground. The support of four strain monopodia makes the measuring platform more rigid. The optimal structural parameters of the strain monopodia are obtained adopting response surface methodology, which allows the sensitivity and stiffness of the platform to be balanced. D optimization is adopted to obtain a more accurate calibration matrix from the redundant outputs and thus improve the measurement accuracy of the platform. Model simulation results show that the load capacity of the measurement platform is more than 1000 kg. Using the results of theoretical analysis, a prototype system was fabricated and tested. The experimental results show that the fundamental frequency of the platform is 749.5 Hz, the dynamic relative error is less than 5.6 % in the frequency range of 3–300 Hz, and the static relative error is less than 5 %. The linearity of the generalized force is within 1.5 %FS, and the repeatability is within 1.1 %FS.